Community Service Research (CSR) In Corn Chips Central Industry, Pandanwangi, Blimbing District,Malang, East Java - Miftahus Saadah; Imam Santoso; Sudarminto Setyo Yuwono (Journal of Innovation and Applied Technology, 2019)
The home industry for processing corn products into corn chips in Malang City includes  Sinar SME and Berkah SME. they both still do not have attractive, innovative and creative packaging designs. The packaging used has not been able to protect the product during the transportation process, and the design is less attractive. Corn chips produced by Sinar and Berkah SME’s did not have a variety flavors of products. This can have an impact on market saturation and reduce sales. There is still a lack of ability in both SME’s people in mastering technology and hygiene. Improvement efforts were made by improving the packaging design of Sinar and Berkah SME’s. The variety of corn chips that can be done to attract consumer appeal is to add a level of spiciness. Technology transfer is carried out in frying equipment and packaging activities using a pedal sealer machine.